LUNG ENDOMETRIOSIS IN THE PHTHISIATRICIAN – PRACTICE - Vorodukhina, A.K.; Boyko, M.G.; Reshetnik, Y.; Dobrovolska, L.; Odintsova, G.A.; Panasenko, T.O. (World of Medicine and Biology, 2012)
The clinical case of lung endometriosis diagnostic in the phthisiatrician practice is presented in this article. There is noticed the necessity of a differential diagnostic between lung tuberculosis and lung endometriosis among reproductive-age women.